Rasch Validation of a Self-Regulation Instrument in Mathematics Learning for Junior High School Students - Aminah Ekawati; Isna Wardiah (Universitas Lambung Mangkurat, 2026)
Although self-regulation instruments have been widely developed, differences in respondent characteristics and the context of the research area require the development of instruments appropriate to the conditions. Nonetheless, few studies have particularly validated self-regulation tools for junior high school children in mathematics learning employing a Rasch measuring approach. This study focuses on developing and validating a self-regulation instrument for junior high school students in mathematics learning through the Rasch model, which involves analyzing reliability, validity, item difficulty levels, and the alignment between respondent abilities and item difficulty levels. The validity consists of item fit and unidimensionality. The instrument was developed through a synthesis of several theoretical frameworks and simplified into three main dimensions, namely cognitive and metacognitive regulation, motivational and emotional regulation, and behavioral and social regulation, which consisted of 12 four-choice Likert scale statements. The subjects of this research were 60 eighth-grade students at a public junior high school in Banjarmasin City. Data analysis was performed using Winsteps 4.7.0 and RStudio 4.5.2 software. The results of the analysis showed that the instrument had good reliability, namely Cronbach's Alpha = 0.869, WLE Reliability = 0.873, and EAP Reliability = 0.872, and satisfactory construct validity, supported by acceptable item fit and unidimensionality based on PCA of residuals. These findings support the unidimensionality of self-regulation within a Rasch framework in mathematics learning and present a context-specific validated instrument with three dimensions, operationalized into 12 theoretically grounded items for diagnosis.